Determining the Number of Factors to Retain in EFA: An easy-to-use computer program for carrying out Parallel Analysis - Ledesma, Rubén Daniel; Valero-Mora, Pedro (Practical assessment, research & evaluation, 2007)
Parallel Analysis is a Monte Carlo simulation technique that aids researchers in determining the number of factors to retain in Principal Component and Exploratory Factor Analysis. This method provides a superior alternative to other techniques that are commonly used for the same purpose, such as the Scree test or the Kaiser's eigenvalue-greater-than-one rule. Nevertheless, Parallel Analysis is not well known among researchers, in part because it is not included as an analysis option in the most popular statistical packages. This paper describes and illustrates how to apply Parallel Analysis with an easy-to-use computer program called ViSta-PARAN. ViSta-PARAN is a user-friendly application that can compute and interpret Parallel Analysis. Its user interface is fully graphic and includes a dialog box to specify parameters, and specialized graphics to visualize the analysis output.